APERTURE SHAPING FOR TWO LINE RESOLUTION IN THE APODISED VARIABLE COHERENCE IN THE PRESENCE OF PRIMARY SPHERICAL ABERRATION - Kumar, T.Kiran; Narsaih, A.; Sagar, D. Karuna (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Aperture is one of the most basic optical elements which are often encountered in optical systems. A plane wave diffracted by an aperture is a typical diffraction problem which has been widely treated and the propagation characteristics of a beam limited with an aperture are well revealed and understood. When the sizes of aperture are much larger than the light wavelength of the incident plane wave the scalar paraxial diffraction theory is usually useable because the scalar description of the diffracted plane wave is easy and acceptable.